Large-Area Two-Dimensional Layered MoTe$_2$ by Physical Vapor Deposition and Solid-Phase Crystallization in a Tellurium-Free Atmosphere - Huang, Jyun-Hong; Deng, Kuang-Ying; Liu, Pang-Shiuan; Wu, Chien-Ting; Chou, Cheng-Tung; Chang, Wen-Hao; Lee, Yao-Jen; Hou, Tuo-Hung (2017)
Advanced Materials Interfaces,1700157, 2017 Molybdenum ditelluride (MoTe$_2$) has attracted considerable interest for nanoelectronic, optoelectronic, spintronic, and valleytronic applications because of its modest band gap, high field-effect mobility, large spin-orbit-coupling splitting, and tunable 1T'/2H phases. However, synthesizing large-area, high-quality MoTe$_2$ remains challenging. The complicated design of gas-phase reactant transport and reaction for chemical vapor deposition or tellurization is nontrivial because of the weak bonding energy between Mo and Te. Here, we report a new method for depositing MoTe$_2$ that entails using physical vapor deposition followed by a post-annealing process in a Te-free atmosphere. Both Mo and Te were physically deposited onto the substrate by sputtering a MoTe$_2$ target. A composite SiO$_2$ capping layer was designed to prevent Te sublimation during the post-annealing process. The post-annealing process facilitated 1T'-to-2H phase transition and solid-phase crystallization, leading to the formation of high-crystallinity few-layer 2H-MoTe$_2$ with a field-effect mobility of ~10 cm$^2$/(V-s), the highest among all nonexfoliated 2H-MoTe$_2$ currently reported. Furthermore, 2H-MoS$_2$ and Td-WTe$_2$ can be deposited using similar methods. Requiring no transfer or chemical reaction of metal and chalcogen reactants in the gas phase, the proposed method is potentially a general yet simple approach for depositing a wide variety of large-area, high-quality, two-dimensional layered structures.